The regulatory role of cystatin C in autophagy and neurodegeneration - T. A. Korolenko; A. B. Shintyapina; A. B. Pupyshev; A. A. Akopyan; G. S. Russkikh; M. A. Dikovskaya; V. A. Vavilin; E. L Zavjalov; M. A. Tikhonova; T. G. Amstislavskaya (Вавиловский журнал генетики и селекции, 2019)
Autophagy is a dynamic cellular process involved in the turnover of proteins, protein complexes, and organelles through lysosomal degradation. It is particularly important in neurons, which do not have a proliferative option for cellular repair. Autophagy has been shown to be suppressed in the striatum of a transgenic mouse model of Parkinson’s disease. Cystatin C is one of the potent regulators of autophagy. Changes in the expression and secretion of cystatin C in the brain have been shown in amyotrophic lateral sclerosis, Alzheimer’s and Parkinson’s diseases, and in some animal models of neurodegeneration, thus proving a protective function of cystatin C. It has been suggested that cystatin C plays the primary role in amyloidogenesis and shows promise as a therapeutic agent for neurodegenerative diseases (Alzheimer’s and Parkinson’s diseases). Cystatin C colocalizes with the amyloid β-protein in the brain during Alzheimer’s disease. Controlled expression of a cystatin C peptide has been proposed as a new approach to therapy for Alzheimer’s disease. In Parkinson’s disease, serum cystatin C levels can predict disease severity and cognitive dysfunction, although the exact involvement of cystatin C remains unclear. The aim: to study the role of cystatin C in neurodegeneration and evaluate the results in relation to the mechanism of autophagy. In our study on humans, a higher concentration of cystatin C was noted in cerebrospinal fluid than in serum; much lower concentrations were observed in other biological fluids (intraocular fluid, bile, and sweat). In elderly persons (61–80 years old compared to practically healthy people at 40–60 years of age), we revealed increased cystatin C levels both in serum and intraocular fluid. In an experiment on C57Bl/6J mice, cystatin C concentration was significantly higher in brain tissue than in the liver and spleen: an indication of an important function of this cysteine protease inhibitor in the brain. Using a transgenic mouse model of Parkinson’s disease (5 months old), we demonstrated a significant increase in osmotic susceptibility of brain lysosomes, depending on autophagy, while in a murine model of Alzheimer’s disease, this parameter did not differ from that in the appropriate control.